2018
DOI: 10.1097/meg.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin in nonalcoholic fatty liver disease: hit multiple targets with a single shot

Abstract: Rifaximin therapy appears to be effective and safe in modifying NASH through reduction of serum endotoxin and improvement of insulin resistance, proinflammatory cytokines, CK-18, and NAFLD-liver fat score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 42 publications
2
53
0
1
Order By: Relevance
“…Rifaximin is a minimally absorbable antibiotic, which has been shown to be effective in patients with NAFLD by improving liver enzymes and decreasing NAFLD fat score. Further research is ongoing, studying the role of intestinal microbiota in the pathogenesis of NAFLD [72]. Oxidative stress has also been shown to be a significant risk factor of NAFLD.…”
Section: Risk Profiling For Nafldmentioning
confidence: 99%
“…Rifaximin is a minimally absorbable antibiotic, which has been shown to be effective in patients with NAFLD by improving liver enzymes and decreasing NAFLD fat score. Further research is ongoing, studying the role of intestinal microbiota in the pathogenesis of NAFLD [72]. Oxidative stress has also been shown to be a significant risk factor of NAFLD.…”
Section: Risk Profiling For Nafldmentioning
confidence: 99%
“…Gangarapu et al have demonstrated that a short-term administration of rifaximin (1200 mg/day for 28 days) improved the clinical status of patients with NAFLD/NASH, which was associated with reduced serum transaminases and circulating endotoxins [76]. Abdel-Razik et al reported that after rifaximin therapy (1100 mg/day for 6 months), patients with NASH showed significantly reduced levels of proinflammatory cytokines, ALT, and NAFLD-liver fat score [77]. However, in an open-label clinical trial, rifaximin administration (800 mg/day for 6 weeks) was not effective for humans with NASH [78].…”
Section: Therapeutic Approach To Reducing Lipopolysaccharides In Nafldmentioning
confidence: 99%
“…Antibiotics efficacy of treating NAFLD has been demonstrated in various studies. Several clinical investigations indicated that short-term administration of rifaximin appeared to significantly improve NAFLD with reduced circulating endotoxins and serum transaminases (Gangarapu et al, 2015;Abdel-Razik et al, 2018). However, one clinical trial presented opposite results.…”
Section: Antibioticsmentioning
confidence: 99%